2014
DOI: 10.1115/1.4028536
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Semiphenomenological Model of a Half-Sarcomere for Real-Time Prediction of Mechanical Behavior

Abstract: With existent biomechanical models of skeletal muscle, challenges still exist in implementing real-time predictions for contraction statuses that are particularly significant to biomechanical and biomedical engineering. Because of this difficulty, this paper proposed a decoupled scheme of the links involved in the working process of a sarcomere and established a semiphenomenological model integrating both linear and nonlinear frames of no higher than a second-order system. In order to facilitate engineering ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…As presented in the earlier work [19], the harmonic oscillator hypothesis also leads to another characteristic quantity of "natural frequency" of EMG signal, the physical meaning of which is still under investigation, but initial analysis showed that this natural frequency is independent of MU firing rate, further supporting the oscillator hypothesis of EMG. The semiphenomenological model can be used as a cybernetic model because the inputs and outputs of the model are all external measureable quantities, and linear frames are extracted from basic in vitro experimental data, ensuring the high computational efficiency for engineering applications [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As presented in the earlier work [19], the harmonic oscillator hypothesis also leads to another characteristic quantity of "natural frequency" of EMG signal, the physical meaning of which is still under investigation, but initial analysis showed that this natural frequency is independent of MU firing rate, further supporting the oscillator hypothesis of EMG. The semiphenomenological model can be used as a cybernetic model because the inputs and outputs of the model are all external measureable quantities, and linear frames are extracted from basic in vitro experimental data, ensuring the high computational efficiency for engineering applications [13].…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of biophysics, the boundary between cybernetic and biomechanical models of muscle is very dim, while the word "cybernetic" here refers to a model that can take effect in practical engineering. For this purpose, a semiphenomenological model was developed in our previous work [13] to derive an engineering-oriented cybernetic model.…”
Section: Cybernetic Model Of Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…In order to better interpret the mechanism of human-exoskeleton interaction, the SP muscular model which aims at concise structure, high efficiency, and comprehensive descriptive function is applied here [31].…”
Section: Sp Model-based Human-exoskeleton Interaction Mechanism Intermentioning
confidence: 99%
“…In the proposed model, interactive force is applied as the measurement model output and the EMG signal is used as the state model input to indicate muscle activation. Hill's muscle model and semi-phenomenological (SP) model [31] are adopted to acquire the forward dynamics of joint motion for the state model and the human-machine interaction mechanism interpretation for the measurement model, respectively. In practical applications, the GP-based NARX model and back propagation neural network (BPNN) are applied to provide better flexibility and adaptivity.…”
Section: Introductionmentioning
confidence: 99%